Balance Markers in Adolescents at 1 Month Postconcussion. Issue 3 (17th March 2017) - Rochefort, Coralie; Walters-Stewart, Coren; Aglipay, Mary; Barrowman, Nick; Zemek, Roger; Sveistrup, Heidi
Background: The Balance Error Scoring System (BESS) shows that balance tends to recover within days after a concussion, whereas measures of the movement of the center of pressure (COP) show that balance deficits can persist up to 1 month after concussion. While approximately 30% of adolescents suffering concussion have functional consequences including balance deficits, evidence of the use of different balance assessments for concussion is limited within this population. Purpose: To compare performance on a series of balance assessments between adolescents with a diagnosed concussion at 1 month postinjury and noninjured control participants within the same age distribution. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Thirty-three adolescents 1 month postconcussion and 33 control participants completed the BESS followed by two, 2-minute trials standing on a Nintendo Wii Balance Board (WBB), during which the COP under their feet was recorded using 2 testing protocols: (1) double-leg stance, eyes open (EO) and (2) double-leg stance, eyes closed (EC). Participants then completed a dual-task condition (DT) with eyes open combining a double-leg stance and a Stroop color and word test while standing on the WBB. Three commonly used COP variables, anterior-posterior (A/P) and mediolateral (M/L) velocity and 95% ellipse, were computed for each condition performed on the WBB. Results: Participants postconcussion swayed over a significantly larger ellipse area compared with the control group in the EO ( P = .008), EC ( P = .002), and DT ( P = .003) conditions and also performed the DT condition with faster COP velocity in the M/L direction ( P = .007). No significant group difference was identified for BESS total score. Conclusion: At 1 month postconcussion, participants continued to demonstrate balance deficits in COP control despite scoring similar to controls on the BESS. Simple COP measures of balance may identify subtle impairments not captured by the BESS.